Enhancement of Voltage Stability by Using SVC for 30-Bus Power System - Amin, Dara Hama (Kurdistan Journal of Applied Research, 2019)
Voltage stability refers to maintaining the value of the voltage in all busses of the electric network at a steady level (initial operating point) during any sudden disturbance. Voltage instability may happen due to an increase in the demand of the load or in case of any change in the reactive power, thus, the system will go into uncontrollable and unstoppable decline in the voltage level. The effect of Static Var Compensator (SVC) on voltage stability is discussed in the paper, as well as the improvement of the voltage profile. Usually, SVC and FACTS devices were used for enhancing the voltage level profile and so the stability. Choosing the optimal location for the FACTS devices is essential due to its expensive costs. This paper used sensitivity factor to helpful to determine the most correct placement of FACTS devices in the system. Simulations are performed on Kurdistan Region 30-bus Power System using MATLAB-PSAT tool. As a result, the voltage of all 30 buses calculated. Based on the “voltage sensitivity factor”, the nominated weak buses has been marked which are suitable for placing the FACTS devices in order to improve the limits of the voltage stability of the system. Moreover, depending on the obtained optimal locations, a full analysis of the voltage and powers for the system has applied in two cases, before and after placing SVC respectively which is result in notable stability improvement and losses reduction.